Understand mental health impact of pandemic on student‐athletes, sports medicine staff. Issue 2 (16th May 2021) - Neal, Timothy; Quandt, Eric; Thornton, James; Tucker, James
Abstract : The COVID‐19 pandemic had an entirely unexpected impact on the world, including intercollegiate athletics. Beyond the loss of life and disruption of daily routines and athletic schedules, a severe and lasting effect of the COVID‐19 pandemic is the mental health challenges faced by millions of people, including those in intercollegiate athletics.